CORPORATE CITIZENSHIP IN A GLOBAL CONTEXT - MARWAHA, KANWAL (IJRDO - Journal of Social Science and Humanities Research, 2017)
Corporate Citizenship (CC) highlight the new political role of corporations in society by arguing that corporations increasingly act as quasi-governmental actors and take on what hitherto had originally been governmental tasks. By examining political and sociological citizenship theories, the authors show that a corporate engagement can be explained by a changing (self-) conception of corporate citizens from corporate bourgeois to corporate citizen. The corporate citizen assumes co-responsibilities for social and civic affairs and actively collaborates with fellow citizens beyond governmental regulation. This change raises the question of how such corporate civic engagement can be aligned with public policy regulations and how corporate activities can be integrated into the democratic regime. By referring to the renewed European Union strategy for Corporate Social Responsibility, the authors show how such a subsidiary corporate-governmental task-sharing can be organized. the apparent demise of the concept of corporate social responsibility and its usurpation within academic literature, managerial practice and policy debate, by the concept ofcorporate citizenship. Having failed in its attempt to compel companies to behave responsibly, corporate social responsibility has been superseded by a more consensual approach that seeks to encourage companies to behave good corporate citizens. The role envisaged for corporate citizenship by this article is illustrated by an account of the United Nations Global Compact and concerns the  establishment, through consensual means, of the norms necessary for an effective regime of corporate social responsibility.